The interplay between T helper cells and brain barriers in the pathogenesis of multiple sclerosis - Angelini, Gabriele; Bani, Alessandro; Constantin, Gabriela; Rossi, Barbara (Frontiers in Cellular Neuroscience, 2023)
The blood-brain barrier (BBB) and the blood-cerebrospinal fluid barrier (BCSFB) represent two complex structures protecting the central nervous system (CNS) against potentially harmful agents and circulating immune cells. The immunosurveillance of the CNS is governed by immune cells that constantly patrol the BCSFB, whereas during neuroinflammatory disorders, both BBB and BCSFB undergo morphological and functional alterations, promoting leukocyte intravascular adhesion and transmigration from the blood circulation into the CNS. Multiple sclerosis (MS) is the prototype of neuroinflammatory disorders in which peripheral T helper (Th) lymphocytes, particularly Th1 and Th17 cells, infiltrate the CNS and contribute to demyelination and neurodegeneration. Th1 and Th17 cells are considered key players in the pathogenesis of MS and its animal model, experimental autoimmune encephalomyelitis. They can actively interact with CNS borders by complex adhesion mechanisms and secretion of a variety of molecules contributing to barrier dysfunction. In this review, we describe the molecular basis involved in the interactions between Th cells and CNS barriers and discuss the emerging roles of dura mater and arachnoid layer as neuro-immune interfaces contributing to the development of CNS inflammatory diseases.